2014
DOI: 10.3390/pharmacy2030248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a Physical Assessment Course on the Practice of Institutional Pharmacists

Abstract: Abstract:We aimed to assess the impact of a professional development course on clinical pharmacists' level of confidence using physical assessment (PA) and whether it resulted in changes to their clinical practice. Workshop participants were asked to complete a pre-workshop survey, as well as three post-workshop surveys, to assess the pharmacists' level of confidence in PA. Pharmacists were also asked about their integration of PA skills and use of Additional Prescribing Authority (APA). Pharmacists' confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…All three studies involving practicing pharmacists reported this outcome 25‐27 . Practicing pharmacists' confidence with performing physical assessment improved from precourse to postcourse surveys in two studies 25,26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All three studies involving practicing pharmacists reported this outcome 25‐27 . Practicing pharmacists' confidence with performing physical assessment improved from precourse to postcourse surveys in two studies 25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Two authors (A. R. B. and R. D. T.) then independently screened the 552 remaining citations, and 28 underwent full text review. Sixteen studies met the inclusion criteria 12‐27 . The corresponding authors of three studies 22,24,26 were contacted via email and provided additional information about their methodology and results, and data from three studies were available to reviewers 23,25,27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a second study, by Breault, et al, which assessed licensed pharmacist’s impressions of physical assessment skills in an institutional setting before and after a workshop, the most common barriers identified as to why physical assessment is not performed in practice were: lack of comfort, lack of training, and deeming it unnecessary since other professionals complete this skill [ 24 ]. Additionally, when pharmacists scored their level of comfort before the workshop, the average score was a one, which translated to “not confident” in performing physical assessments [ 25 ]. Finally, in a study by Chevalier et al, where physicians and nurses were surveyed on the services that clinical pharmacists provide, none of the physicians surveyed indicated that having pharmacists complete physical assessment would be beneficial to their practice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%